2007
DOI: 10.1007/s00425-007-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

High frequency (900 MHz) low amplitude (5 V m−1) electromagnetic field: a genuine environmental stimulus that affects transcription, translation, calcium and energy charge in tomato

Abstract: Using an especially-designed facility, the Mode Stirred Reverberation Chamber, we exposed tomato plants (Lycopersicon esculentum Mill. VFN8) to low level (900 MHz, 5 V m(-1)) electromagnetic fields for a short period (10 min) and measured changes in abundance of three specific mRNA soon after exposure. Within minutes of electromagnetic stimulation, stress-related mRNA (calmodulin, calcium-dependent protein kinase and proteinase inhibitor) accumulated in a rapid, large and 3-phase manner typical of an environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 43 publications
(41 reference statements)
7
58
0
3
Order By: Relevance
“…Previous work from our group demonstrated an unequivocal link between low amplitude, short duration HF EMF exposure and stress-related mRNA accumulation in tomato plants [Roux et al, , 2008Vian et al, 2006;Beaubois et al, 2007], which showed very similar characteristics to those observed after injurious treatments [Vian et al, 1999]. We proposed that plants, especially leaves, have an architecture (planar surfaces) designed to maximize acquisition of matter (gases), energy (sunlight), and information (e.g., EMF) from their environment .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous work from our group demonstrated an unequivocal link between low amplitude, short duration HF EMF exposure and stress-related mRNA accumulation in tomato plants [Roux et al, , 2008Vian et al, 2006;Beaubois et al, 2007], which showed very similar characteristics to those observed after injurious treatments [Vian et al, 1999]. We proposed that plants, especially leaves, have an architecture (planar surfaces) designed to maximize acquisition of matter (gases), energy (sunlight), and information (e.g., EMF) from their environment .…”
Section: Discussionmentioning
confidence: 64%
“…Using tomato plants as a model system and a mode stirred reverberation chamber (MSRC) as the facility for exposing them to defined doses of HF EMF, our group recently pointed out that a short (10 min), high frequency (900 MHz), low amplitude (5 V/m) EMF exposure caused rapid (15 min), transient and strong (4.5-fold) increases of at least 5 stressrelated transcripts (bZIP transcription factor, calmodulin, calcium-dependant protein kinase, chloroplast mRNA binding protein and proteinase inhibitor 2) Vian et al, 2006]. The EMF exposure was also followed by a large decrease (40%) in ATP content [Roux et al, 2008]. These responses were highly dependent on physiological levels of Ca 2þ and were totally prevented by treatment with calcium-counteracting drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the research programs concerned by in vitro experiments led under investigation various types of exposure systems [16], the MSRC were very seldom used [2]. Previously, we identified a formal link between an electromagnetic environment (900 MHz) and the response of a plant model [17][18][19][20] from MSRC experiments. However, the interest of this exposure device for in vitro experiments is highlighted here in the case of human skin cells in culture.…”
Section: Exposure Setups For Bioelectromagnetic Experiments In High Fmentioning
confidence: 99%
“…VFN8) ñà ïîëó÷åíè äîêàçàòåëñòâà, ÷å òå âúçïðèåìàò è ðåàãèðàò íà ÅÌÏ êàòî íà óâðåaeäàíå (íàðàíÿâàíå). Âèñîêî-÷åñòîòíîòî ÅÌÏ å ñòèìóë, êîéòî ïîâëèÿâà ãåííàòà åêñïðåñèÿ, òðàíñêðèïöèÿòà, òðàíñëàöèÿòà, êàêòî è íèâàòà íà êàëöèé è åíåðãèéíèÿ áàëàíñ íà äîìàòåíèòå ðàñòåíèÿ [Beaubois, 2007;Roux, 2008;Vian, 2006].…”
Section: âúâåäåíèåunclassified